The population status, breeding success and diet of Subantarctic Skuas two decades after the feral cat eradication on Marion Island - Cerfonteyn, Mia Elizabeth (Percy FitzPatrick Institute of African Ornithology, 2014)
Prey availability is often the driver behind predator population trends, diet and breeding success. Changes in predator abundance and breeding success represent numerical responses to changes in prey abundance, whereas dietary shifts can be classified as functional responses. Invasive mammals introduced to island ecosystems can have detrimental impacts on endemic bird populations and thus disrupt predator-prey relationships. In cases where a predator is dependent on a certain prey species, the distribution, abundance, breeding success and diet of a predator can reveal disruptions in their prey abundance and density.